Wide intra- and inter-country variability in drug use and dosage in very-low-birth-weight newborns with severe infections - Pandolfini, Chiara; Kaguelidou, Florentia; Sequi, Marco; Jacqz-Aigrain, Evelyne; Choonara, Imti; Turner, Mark A.; Manzoni, Paolo; Bonita, Maurizio (Springer, 2013)
Purpose: To describe the use of ciprofloxacin and fluconazole for the treatment of sepsis in European neonatal intensive care units (NICUs) in order to better orient research aimed at acquiring essential knowledge in this critical area. Methods: The survey consisted of an online questionnaire for all participating NICUs on treatment schemes employed, rationales behind drug choices and interest in participation in research involving the two drugs. Results: A total of 189 level II and III NICUs participated in the survey, representing 25 countries, with Italy, UK and France providing the greatest number of centres (54% of total). Ciprofloxacin is used in 25% of NICUs that responded, although the indications for administering it vary between centres and the dosage ranges vary considerably, with 25% of NICUs giving ≤10 mg/kg/day and another 25 % giving ≥21 mg/kg/day. Factors given as affecting the decision to use ciprofloxacin are uncertainty about its safety and pharmacokinetics and level of penetration in the cerebrospinal fluid. Among the 70% of responding units that use fluconazole to treat fungal infection, 45% administer 6 mg/kg unit doses while 33% administer 12 mg/kg; 41% of NICUs use a 24-h interval between administrations while 20% wait 72h. Among the responding NICUs, 57% were willing to participate in a project on ciprofloxacin and 59% would consider participating in a randomized controlled trial evaluating fluconazole versus micafungin. Conclusions: Great variability in therapies exists within and between countries. Numerous centres are interested in participating in research on these drugs, highlighting the need for further knowledge on sepsis treatment and European centres’ interest in off-patent medicine research.